Influence of climatic variables on the incidence of meningitis and its space distribution in the city of Ponta Grossa-PR, 2001-2005 - Stocco, Caroliny; Leite, Maysa de Lima; Labiak, Valéria Beatris; Virgens Filho, Jorim Sousa das; Nascimento, Éderson (Saúde e Sociedade, 2010)
Climatic elements have an important influence on the manifestation of many human diseases. The objective of this study was to evaluate the influence of local climate variables on the monthly incidence of meningitis in the city of Ponta Grossa, State of Paraná, in the period from 2001 to 2005, and to spatially distribute its occurrence in the urban area. The initial sample was composed of 401 notified cases which were confirmed as being of resident citizens in this city. Strong correlation was verified between the average monthly incidence of meningitis and the following climate variables: mean air temperature, precipitation and relative humidity in most months. The spatial distribution of the cases under study showed higher concentration in the central-west and north-central portions of the city.